Non-governmental Enforcement of EU Environmental Law: A Stakeholder Action for Wolf Protection in Finland - Epstein, Yaffa; Kantinkoski, Sari (Frontiers in Ecology and Evolution, 2020)
In a recent decision, the Court of Justice of the EU (CJEU) sided with a small regional Finnish nature protection organization, Tapiola, interpreting EU law to require an end to wolf hunting in Finland. Much of the hunting of wolves and other large carnivores throughout the EU will also be impacted by this decision. Through this case, local stakeholders were able to utilize EU law to access national courts as well as the EU courts, to bring about national compliance with EU species protection law. This article analyzes the process of using law as a tool for environmental protection in the EU, and the challenges and opportunities therein. It also illuminates the different roles and outcomes for stakeholders in pursuing national compliance with EU law in direct actions and references for preliminary rulings.